Primary reconstruction of alveolar clefts using recombinant human bone morphogenic protein-2: clinical and radiographic outcomes - Fallucco, Michael A; Carstens, Michael H (The Journal of craniofacial surgery, 2009)
This novel method for primary alveolar cleft bony reconstruction avoids donor site morbidity and does not require close approximation of alveolar segments as necessitated by gingivoperiosteoplasty. The study aims to provide radiographic evidence of de novo synthesis of bone using recombinant human bone morphogenic protein-2 (rhBMP-2). This institutional review board-approved class IV study retrospectively evaluated primary alveolar cleft patients from 2004 to 2006. Subjects chose an off-label application of rhBMP-2 impregnated on an absorbable collagen sponge carrier to reconstruct alveolar clefts, all greater than 3 mm in width. The surgical technique used for soft tissue closure, developmental field reassignment, is not a gingivoperiosteoplasty and is applicable to alveolar clefts of virtually any size. Developmental field reassignment produces a periosteal "pocket" containing mesenchymal stem cells sensitive to cytokines, such as BMP-2. Inductive conversion of mesenchymal stem cells to osteoblasts by BMP-2 is known as in situ osteogenesis (ISO). Seventeen cleft sites treated with ISO were evaluated at 6 months postoperative using low-dose spiral computed tomography with 1-mm cuts limited to the maxilla. Alveolar bone density (Hounsfield units) was assessed by 3 radiologists; trabecular bone was defined as Hounsfield units of more than 226. In 16 of 17 cleft sites, ISO produced trabecular bone that filled the implantation site both transversely and vertically. Stem cell stimulation using rhBMP-2/absorbable collagen sponge offers highly effective radiographic and clinical unification of the dental arch without donor site morbidity. Long-term follow-up studies for this initial cohort are under way to examine information on orthodontic relationships and cephalometrics using cone-beam computed tomography technology.